Listening Again to the Text : New Testament Studies in Honor of George Lyons - Thompson, Richard P. (Claremont studies in New Testament & Christian origins, 2020)
"This volume explores the Greco-Roman and Jewish origins of the New Testament and early Christianity. It pays particular attention to the gospels and the traditions which place those sacred texts."--Publisher statement